VD_FINDINFO Jug / 2015 / 218 vom 30. Januar 2015 - VD Tribunal cantonal (2015)
CONSTATATION DES FAITS, IN DUBIO PRO REO, ACQUITTEMENT, FRAIS DE LA PROCÉDURE, PLAIGNANT | 10 CPP (CH), 398 al. 3 let. b CPP (CH), 427 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)